The Influence of Self-Serving Leadership on Deviant Behaviors in the Workplace: A Moderated Mediation Model - Liu, Liangcan; Wan, Zhitao; Lin, Yanping; Wang, Xu (Frontiers in Psychology, 2022)
Self-serving leadership is a typical example of destructive leadership that has negative effects on its subordinates and organization. According to social identity theory, we propose a theoretical model that self-serving leadership induces employee interpersonal deviance and organizational deviance through organization identification, and we explore the moderating role of moral identity in this relationship. Based on survey data collected from 377 questionnaires by using a three-wave time-lagged design, structural equation modeling results showed that (1) there was a significant positive correlation between self-serving leadership and employees’ deviant behavior, (2) organizational identification partially mediates the relationship between self-serving leadership and employees’ deviant behavior, and (3) employees’ moral identity negatively moderates the relationship between self-serving leadership and employees’ organizational identification. The findings further extend the research on the influence of self-serving leadership on employee workplace deviance. They also reveal the mechanisms and boundary conditions of the effect of self-serving leadership on employee workplace deviance.